Implication et développement professionnel des enseignants dans de nouveaux dispositifs pédagogiques favorisant l’apprentissage du métier d’étudiant - Aurélie Baudier; Emilie Wilmet; Sylviane Bachy (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This article presents and analyzes the implementation of new pedagogical tools to help students succeed that have contributed to the professional development of French-speaking Belgium higher education teachers. Several new workshops co-constructed in collective intelligence with teachers, pedagogical advisors and accompaniers of first-year students focused primarily on the components of benevolence and good classroom climate. A double impact would emerge from this experience: learners would be more involved in their studies and teachers would change their conception of student occupation, their pedagogical approach and their level of interaction.